2018
DOI: 10.1038/s41598-018-32669-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual salience of the stop signal affects the neuronal dynamics of controlled inhibition

Abstract: The voluntary control of movement is often tested by using the countermanding, or stop-signal task that sporadically requires the suppression of a movement in response to an incoming stop-signal. Neurophysiological recordings in monkeys engaged in the countermanding task have shown that dorsal premotor cortex (PMd) is implicated in movement control. An open question is whether and how the perceptual demands inherent the stop-signal affects inhibitory performance and their underlying neuronal correlates. To thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 93 publications
5
15
0
Order By: Relevance
“…In fact, the decrease in the overlap between target and non-target in the mental schema improved the performance, increased the number of neurons that were selective for the target, and anticipated the time of logical target selection. Similar behavioral and neuronal correlates have been observed in the perceptual decision tasks, in which the coherence of moving dots (Hanks and Summerfield, 2017), the proportion of colored dots (Coallier et al, 2015), the proportion of distracting items (Basso and Wurtz, 1997;Schall and Hanes, 1993), and visual salience (Pani et al, 2018;Shen et al, 2010) are manipulated.…”
Section: Comparing Paradigms: Mental Schema-driven Versus Perceptually Driven Decision Makingsupporting
confidence: 61%
“…In fact, the decrease in the overlap between target and non-target in the mental schema improved the performance, increased the number of neurons that were selective for the target, and anticipated the time of logical target selection. Similar behavioral and neuronal correlates have been observed in the perceptual decision tasks, in which the coherence of moving dots (Hanks and Summerfield, 2017), the proportion of colored dots (Coallier et al, 2015), the proportion of distracting items (Basso and Wurtz, 1997;Schall and Hanes, 1993), and visual salience (Pani et al, 2018;Shen et al, 2010) are manipulated.…”
Section: Comparing Paradigms: Mental Schema-driven Versus Perceptually Driven Decision Makingsupporting
confidence: 61%
“…Superior Colliculus (SC) reaches a fixed threshold, while the activity of fixation neurons decreases (Hanes et al, 1998;Paré and Hanes, 2003). However, the control of arm movement tested in equivalent countermanding tasks does not elicit a similar neuronal correlate, especially when tested at the single cell level (Mirabella et al, 2011;Stuphorn, 2015;Pani et al, 2013), and different cortical areas like motor and premotor cortices (especially dorsal premotor cortex, PMd) have been suggested to have a key role in movement inhibition (Mirabella et al, 2011;Mattia et al, 2012;Pani et al 2014;Pani et al 2018;Duque et al, 2012;Duque et al, 2017;Parmigiani and Cattaneo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that salient stimuli enhance response inhibition and trigger earlier and stronger modulation of movement‐related neuronal activity in the premotor cortex (Pani et al, 2018). The advantage of red color in triggering cognitive processes for inhibition of actions might be related to the greater “saliency” of red color.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that salient stimuli enhance response inhibition and trigger earlier and stronger modulation of movementrelated neuronal activity in the premotor cortex (Pani et al, 2018).…”
Section: Response Inhibitionmentioning
confidence: 99%